Cracking and interlayer bonding performance of reinforced asphalt pavements. (31st August 2017) - Raab, Christiane; Arraigada, Martin; Partl, Manfred N.; Schiffmann, Frank
Abstract: Reinforcement of asphalt pavements has become a valuable constructive method for preventing reflective cracking and prolonging service life of roads. Although the overall advantages of these reinforcements seem beyond doubt, there is still lack of information about the actual benefit of different systems on the prolongation of the road's lifespan. Further, it is not clear how they affect the bonding between layers along the pavement's lifetime. This paper investigates the effect of three types of reinforcement systems on the performance of two layered asphalt pavements, mainly considering: (1) Reflective crack propagation. (2) Shear bonding strength. To that end, model and real pavements were constructed in the laboratory and the field using selected reinforcement systems. Designs with various mesh opening sizes and different bond coatings were considered. Afterwards, the pavements were loaded with a down-scaled (MMLS3) and a full-scale (MLS10) traffic load simulator and their performance was compared to pavements without any type of reinforcement. These devices simulate the effect of traffic-similar loading in a compressed period of time. During the loading phase, the crack formation and propagation was monitored through visual inspections and indirectly by measuring the deformation of the pavements with sensors. The interlayer bonding strength was evaluated by coring the pavements and testing the specimens with a Layer Parallel Direct Shear apparatus. Results showed that two reinforcement systems were generally successful in delaying reflective crack propagation. Only one of the systems presented at least similar or even worse performance than the same pavement without reinforcement. On the other hand, it was found that the bonding properties depend on the reinforcement system type, but that in most cases interlayer bond strength was according to the standard requirements.